2015
DOI: 10.3390/ijerph120707647
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dry Eye Syndrome’s and the Likelihood to Develop Sjögren’s Syndrome in Taiwan: A Population-Based Study

Abstract: Background: Dry eye syndrome (DES) is one of the key clinical features and possibly an early clinical presentation of Sjögren’s syndrome (SS). We explore DES prevalence and assess the likelihood of DES patients to develop SS in Taiwan through the National Health Insurance Research Database (NHIRD). Methods: Through a cohort comparison study, longitudinal data from the NHIRD (2000 to 2008) in Taiwan was used to probe the prevalence of DES and the odds that DES patients would later develop SS. Results: The preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…It has been reported that approximately 4.8% of the patients with dry eye may develop SS in about 3.8 years 17. Patients with IBS and FM have similar complaints with SS, such as dry eye and dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that approximately 4.8% of the patients with dry eye may develop SS in about 3.8 years 17. Patients with IBS and FM have similar complaints with SS, such as dry eye and dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Dry eye disease (DED) is a multifactorial disorder of the tear film and ocular surface [3,5]. For many years, researchers have been trying to unveil the core mechanism of DED, which is reflected by the number of publications directly related to dry eye syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that inflammation, such as seen in systemic autoimmune diseases including Sjogren's syndrome and systemic lupus erythematosus, is a common manifestation of dry eye symptoms [4,5]. Some researchers have thus proposed to use topical or systemic immunomodulatory therapy in severe dry eye conditions [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…And the OSDI questionnaire consists of twelve items designed to assess ocular symptoms, vision-related function, and environmental triggers. Based on the OSDI score, the ocular surface was defined as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), or severe [6]. Besides, in order to evaluate the treatment response, patients completed the Subject Global Assessment scale, and clinicians independently assessed patients using the Clinical Global Impression scale.…”
Section: Introductionmentioning
confidence: 99%